POLITICAL SOPHISTICATION AND ITS IMPLEMENTING FACTOR S: THE CASE OF LITHUANIA - Mažylytė, Liucija (Politologija, 2015)
Political sophistication has become an important subject of research since the middle of the 20th century. There is still discussion on how political sophistication is to be defined and how to measure it. However, in Lithuania, this topic has gained little or no attention. It is advantageous to research political sophistication for several reasons. First, it would help to find how well many citizens understand the political processes and what knowledge they have about political parties and politically elite figures. Second, the variable of political sophistication could be further used in the research of political behavior. Finally, it has been claimed that more politically sophisticated people have better understanding about politics, have more information when voting and therefore express their will better. In the first part of this article several conceptions of political sophistication were analyzed. One can conclude it is a broad and multi-dimensional concept and several approaches towards it exist: theories of political psychology, public communication or rational choice theories provide different perspectives. The attitudes evolved from the “classical” one, were that a politically sophisticated person was understood as an individual with the political beliefs system constrained by ideology to more recent one where a politically sophisticated person is supposed to have large amount of political knowledge, to be able to use this information properly and to be willing to gain more of it. If political sophistication is understood more as political knowledge and interest into politics, politically sophisticated ones should be able to recognize important political figures, understand the differences of relevant political parties, know their positions on political issues, now ideologies and be able to locate political parties on ideological scale. Thus they must demonstrate abilities of recognition and understanding as well as active use. However, universal measures of political sophistication could not exist for several reasons. Countries vary in their party and electoral systems, thus different knowledge could be expected, for instance in two-party and multi-party systems. Furthermore, we could not apply all the questions that can be applied for citizens in Western countries (most political sophistication research has been done in the USA) to the case of Lithuania. The classical ideological cleavages can not be easilly found in Lithuanian party system thus citizens could not be able to locate Lithuanian parties on the ideological right/left scale. Additionally, Lithuanian political parties do not express their positions on important political issues as clearly as the Western political parties do; the attitudes also vary among party members. Thus while measuring political sophistication in Lithuania, the questions about party positions on political issues should be avoided (or asked in a different manner than in Western countries). However, in the case of Lithuania, more attention should be paid for factual knowledge questions. More questions about important political figures, party leaders, coalitions, the European Union could be included in future researches. Recent surveys include only few questions about factual knowledge, there are no items to measure how well citizens to apply this knowledge practically. It was advantageous to use data from Representative Lithuanian Citizens’ Survey 2008 for statistical analysis, even if it has some shortages and therefore the results should be treated critically. The index of political sophistication was constructed, where the items of interest into politics and factual political knowledge were included. This helped to rank respondents to four groups: politically unsophisticates (24 %), low politically sophisticates (29.7 %), mediate political sophisticates (34.7%) and high political sophisticates (11.6 %). This measurement differentiates the respondents well. The other aspect of political sophistication analyzed in this article is factors that influence level of political sophistication. It can be effected by structural factors such as party or electoral system. Importance of individual level resources or abilities that individual can use and that can influence his political sophistication. Attention is paid to several individual-level factors such as person’s education, income, usage of informational media resources, discussions with the other people, gender and age. Three hypotheses were tested and relatively proved using data from Representative Lithuanian Citizens’ Survey 2008. Individuals that discuss political issues with the others, use more information resources and have higher education tend to be more politically sophisticated. However, socioeconomic variables such as age, gender and income also have impact on one’s level of political sophistication. The regression analysis showed that the factor that has most influence on political sophistication is age. Discussions with other people about politics, education, usage of informatikon resources and income have less impact. Thus even this empirical research is limited, several tendencies could be seen. Improving measurement tools and examining the effect of citizens’ political sophistications effect on their political behavior could be future research topics.